Acute dysphagia: an unusual treatable cause. Issue 11 (22nd October 2007) - Mathers, Jonathan; Banerjee, Ashis; Mbamalu, David
Abstract : Bariatric surgery is a rapidly expanding surgical sub-speciality, with a large proportion of the relevant surgical procedures being performed in the private sector. Acute complications of newer surgical procedures can lead to emergency department presentation, with which the staff may be unfamiliar. A 34-year-old woman was seen in the emergency department with acute total dysphagia following laparoscopic adjustable gastric banding, which was treated successfully by a simple bedside procedure.